2023
DOI: 10.1002/ep.14132
|View full text |Cite
|
Sign up to set email alerts
|

Fabricated design of hydrotalcite embedded lanthanum organic frameworks for defluoridation of water

Abstract: The surplus fluoride in drinking water leads to diseases namely fluorosis (dental, skeletal, and non‐skeletal). Hence, to overcome these problems, in this study, hydrotalcite (HT) integrated La‐based metal‐organic frameworks (LaMOFs) namely HT‐LaMOFs was fabricated for fluoride removal. The fabricated HT‐LaMOFs material was well characterized by various characterization methods (x‐ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), Energy‐dispersive X‐ray … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 81 publications
0
1
0
Order By: Relevance
“…30 Jeyaseelan et al developed hydrotalcite/cerium organic framework-entrapped biopolymers and hydrotalciteloaded lanthanum organic frameworks for fluoride adsorption studies. 31,32 He et al reported La-and Cemodified alumina for promising fluoride removal applications. 33 Debroy et al reported rare earth metal oxide nanoparticles for As(III) and fluoride removal from water.…”
Section: Introductionmentioning
confidence: 99%
“…30 Jeyaseelan et al developed hydrotalcite/cerium organic framework-entrapped biopolymers and hydrotalciteloaded lanthanum organic frameworks for fluoride adsorption studies. 31,32 He et al reported La-and Cemodified alumina for promising fluoride removal applications. 33 Debroy et al reported rare earth metal oxide nanoparticles for As(III) and fluoride removal from water.…”
Section: Introductionmentioning
confidence: 99%